ANALISIS PENGARUH DIMENSI FRAUD TRIANGLE TERHADAP PERILAKU KECURANGAN AKADEMIK SELAMA MASA PANDEMI COVID 19 - Siswanto, Victorianus Aries (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
During the Covid-19 pandemic, almost all schools and universities used an online system in their teaching and learning processes. However, with this online system, various frauds appear in the world of education. Cheating is carried out including copy and paste, sharing answers with each other, copying friends' tasks and so on. From this phenomenon, it is necessary to conduct research to examine the factors that affect academic fraud by using the Fraud Triangle dimensions including Pressure, Opportunity, and Rationalization. Data collection in this study used observation methods and questionnaires that were distributed to active students in the STMIK Undergraduate Program using random sampling techniques. Data processing and analysis is assisted with the SPSS program. Before processing the data, validity, reliability, and normality tests are carried out. This study used F Test and t Test with an error degree of 5%. The conclusion of this study was that the pressure and rationalization variables have no effect on academic cheating, while the opportunity variables have an effect on academic cheating. But overall (F Test), it was found that all variables, pressures, opportunities, and rationals simultaneously (together) affect the academic cheating. These shows that although pressure and rationalization do not affect students to commit fraud, broadly speaking, undergraduate students at STMIK Widya Pratama Pekalongan have a fairly high awareness that these things are actions that are not allowed both ethically and legally in terms of existing legal norms. Keywords : Academic cheating, Dimensions of Fraud Trianggle, Pressure, Opportunity and Rationalization